DIAGNOSTIC ACCURACY OF BOEY SCORE TO PREDICT 30 DAYS MORTALITY IN PERFORATED PEPTIC ULCER PATIENTS - WASEEM, S; YAQUB, K; AKRAM, W; MEMON, ZA; AHSAN, A; TURAB, UA; RAJPUT, IA; KHAN, NA (Biological and Clinical Sciences Research Journal, 2024)
Perforated peptic ulcers remain a life-threatening condition despite advancements in surgical and medical treatments. Accurate risk stratification of patients can improve outcomes by guiding clinical decision-making. The Boey scoring system is widely used for predicting mortality in patients with perforated peptic ulcers, yet its diagnostic accuracy warrants further evaluation. Objective: This study aimed to evaluate the diagnostic accuracy of the Boey score in predicting 30-day mortality among patients with perforated peptic ulcers. Methods: This cross-sectional study was conducted at the Department of Surgical Unit VI, Civil Hospital Karachi, over a six-month period from December 7, 2020, to June 7, 2021. A total of 149 patients diagnosed with perforated peptic ulcers were included using non-probability consecutive sampling. The Boey score was calculated for each patient based on preoperative shock, comorbid illness, and duration of perforation >24 hours. The primary outcome measure was 30-day mortality. Descriptive statistics were used to assess the frequency distribution of mortality, and the association between Boey score and mortality was analysed using appropriate statistical methods, with significance set at p < 0.05. Results: The study included 149 patients, with a minimum age of 21 and a maximum age of 50. Of the total, 32 patients (21.5%) experienced 30-day mortality. Among patients with a Boey score of 1, 2.68% had 30-day mortality, and 0.67% of patients with a Boey score of 2 died. Patients with a Boey score of 3 had the highest mortality rate, with 18.1% of this group experiencing 30-day mortality. In contrast, 81.9% of patients with a Boey score of 1 to 3 survived beyond 30 days. Conclusion: The Boey scoring system demonstrated vital predictive accuracy for 30-day mortality in patients with perforated peptic ulcers. This scoring tool effectively identifies high-risk patients, allowing for timely and appropriate management. Despite modern treatment advances, perforated peptic ulcer remains associated with significant mortality, particularly in high-risk patients, as identified by the Boey score.